Evaluation of a Performance-Based Teacher Competency Development Program through the Ruang GTK Platform at SMKN 1 Sengah Temila - Joko Robianto; Imran Imran; Rody Putra Sartika; Afandi Afandi; Marinu Waruwu (Attractive : Innovative Education Journal, 2026)
This study is motivated by the low achievement of the Education Report Card of SMKN 1 Sengah Temila in the aspect of performance-based teacher competence through Ruang GTK, particularly in the dimension of alignment with labor market needs. This condition indicates that the implementation of the performance-based teacher competency improvement program through Ruang GTK has not been optimal. Therefore, this study aims to evaluate the program using a qualitative approach with the CIPP evaluation model. The study involved 42 participants consisting of the principal, vice principals, school supervisors, teachers through snowball sampling. Data were collected through semi-structured in-depth interviews and non-participant observation guided by CIPP instruments to explore program implementation. Documentation was conducted by analyzing supporting documents such as the Education Report Card, employee performance targets, and supervision documents. Data were analyzed using the interactive model of Miles and Huberman through data reduction with coding to identify meaning units and categorize data, followed by data presentation in analytical narratives and thematic matrices, and conclusion drawing through interpretation of patterns. The results showed that in the context aspect, program needs are clear but not yet realized in integrated evidence-based planning. In the input aspect, resources are available but not adequate in quality and distribution. In the process aspect, implementation has been carried out but is not supported by digital-based supervision. Overall, the program has not been optimal and requires continuous improvement through strengthening policies aligned with the school’s vision and mission, improving facilities, program implementation, and follow-up evaluation of Ruang GTK.